(untitled) (Journal of Environmental Science and Natural Resources, 2015)
The effect of municipal solid waste compost, fertilizers, Rhizobium and flora on the growth and yield of wheat was studied through a field experiment at the Soil Science Field Laboratory of Bangladesh Agricultural University, Mymensingh. The soil was silty loam in texture having pH 6.94, organic matter 1.62%, total nitrogen 0.067%, available phosphorus 10.45 ppm, exchangeable K 0.08 me/100g soil, available sulphur 12.00 ppm and cation exchange capacity 15.0 me/100g soil. There were seven treatments such as T0 = control, T1 = 100% recommended doses of fertilizer (RDF), T2 = 100% RDF + compost @ 3.5 t ha-1, T3 = 100% RDF + compost @ 3.5 t ha-1 + Rhizobium, T4 = 75% RDF + 25% N based compost, T5 = 75% RDF + 25% N based compost + Rhizobium, T6 = 100% RDF + Flora. The experiment was laid out in a Randomized Complete Block Design with three replications. Phosphorus, potassium, sulphur, zinc and boron were applied as basal dose from TSP, MOP, gypsum, zinc sulphate and boric acid @ 30 kg P, 135 kg K, 15 kg S, 2 kg Zn and 1 kg B, respectively. Nitrogen as urea was used @100 kg ha-1 for the respective treatments. For T3 and T5, the seeds were inoculated with Rhizobial strains. The plants were harvested at maturity and the grain and straw yields were recorded. Wheat grain and straw samples were collected and analyzed for N,P,K and S. The nutrient uptake of wheat calculated. Application of municipal solid waste compost, fertilizers, Rhizobium and flora increased the N and S content both in grain and straw of wheat but decreased the P content as compared to control. The K content in wheat straw increased with different treatments but the effect was reverse in case of wheat grain. The N,P,K,and S uptake of wheat grain and straw as well as the total uptake increased significantly with all the treatments over control. DOI: http://dx.doi.org/10.3329/jesnr.v6i1.22039 J. Environ. Sci. & Natural Resources, 6(1): 47-52 2013